2015
DOI: 10.3109/00365521.2015.1038848
|View full text |Cite
|
Sign up to set email alerts
|

Sedation during endoscopic retrograde cholangiopancreatography: a randomized controlled study of patient-controlled propofol sedation and that given by a nurse anesthetist

Abstract: PCS with propofol is superior to midazolam and comparable to ACS. PCS resulted in a rapid recovery, fewer respiratory events, and was almost as effective as ACS in ensuring a successful examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 19 publications
1
36
0
2
Order By: Relevance
“…The rate of adverse effects of ERCP (9, 10) and sedation (11, 12) in this study was similar to other studies on the subject. This would lend credence to the notion that the results of this study should be applicable outside the Endoscopy Unit, in which this study was conducted.…”
Section: Discussionsupporting
confidence: 90%
“…The rate of adverse effects of ERCP (9, 10) and sedation (11, 12) in this study was similar to other studies on the subject. This would lend credence to the notion that the results of this study should be applicable outside the Endoscopy Unit, in which this study was conducted.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, PCS is a cost-saving method for sedation during endoscopic procedures that can also improve procedure feasibility and patient satisfaction without affecting patient safety. 14,15 All procedures under PCS might not be possible to continue and require full anaesthesia to complete. With a bedside anaesthetic nurse and an anaesthesiologist immediately available, this can be accomplished.…”
Section: Discussionmentioning
confidence: 99%
“…The economic data from two sedation studies conducted at Linköping University Hospital in Sweden were analysed retrospectively. The first study evaluated ERCP 14 and was conducted at the Surgical Clinic between January 2011 and May 2012. The second study examined bronchoscopy 15 and was conducted at the Department of Pulmonary Medicine between April 2016 and May 2017.…”
Section: Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we added 5 minutes for the start/preparation respectively completion/dismantling of the procedure (10 minutes in total) to the measured procedural time. Our main finding that PCS is a cost-saving method was primarily based on reduced costs for hospital stay and avoidance of aborted procedures that had to be The patients in both studies 3,4 had adequate and sufficient sedation upon insertion of endoscope and during the procedure. The post-procedural assessment by the patients using PCS in both studies showed significantly higher satisfaction of the procedure compared with patients administrated midazolam.…”
Section: Response Letter To the Editormentioning
confidence: 97%